Seizing the opportunity to do things differently: Feminist ideas, policies and actors in UN Women’s ‘Feminist Plan for Sustainability and Social Justice’ - Martínez Franzoni, Juliana (2022)
Since the beginning of the COVID-19 pandemic early in 2020, we have heard global leaders, public intellectuals and civil society activists speaking of a crisis that requires not just ‘building back better’ but rather a radical reconstruction of the pre-pandemic world. Among these, the United Nations (UN) Secretary General has called for a ‘New global Deal’ and a ‘New social contract’ rooted in global solidarity. Such calls contest the idea that the problem is (just) a virus, instead turning our attention to a ‘global social order’ marked by extreme inequalities and concentration of wealth, environmental crisis and a failure of global collective action. They present normative narratives of a future based on justice, ethics and solidarity. But the future cannot just be built on goodwill and hope: a shift of power, not only of narratives, is necessary. Powerful narratives need to be backed up by policy tools, actions and a good sense of the political economy opportunities and constraints for change. In this context, UN Women has produced its Feminist Plan for Sustainability and Social Justice, offering a vision that is bold and ‘feminist’.